Risk factors for colonization and infection by resistant microorganisms in kidney transplant recipients - Monica Taminato; Richarlisson Borges de Morais; Dayana Souza Fram; Rogério Rodrigues Floriano Pereira; Cibele Grothe Esmanhoto; Antonio Carlos Pignatari; Dulce Aparecida Barbosa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to assess the prevalence of colonization and infection by multidrug-resistant bacteria in patients undergoing kidney transplantation and identify the rate of infection, morbidity and mortality and associated risk factors. Methods: a prospective cohort of 200 randomly included kidney transplant recipients. Epidemiological surveillance of the studied microorganisms was carried out in the first 24 hours and 7 days after transplantation. Results: ninety (45%) patients were considered colonized. Female sex, hypertension and diabetes (p<0.005), dialysis time (p<0.004), length of stay after transplantation, delayed renal function, and length of stay were identified as risk factors. The microorganisms were isolated from surgical site, bloodstream and urinary tract infections. Conclusions: colonization by resistant microorganisms in kidney transplant patients was frequent and risk factors associated with infection were identified. The results should guide the care team in order to minimize morbidity and mortality related to infectious causes in this population.